Hubungan Dukungan Keluarga terhadap Kualitas Hidup Pasien ODHA pada Anak - I Made Agus Sudarma Putra; I Ketut Labir; Ni Luh Kompyang Sulisnadewi (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2026)
Human Immunodeficiency Virus (HIV) is a virus that attacks white blood cells and weakens the body's immune system. Children living with HIV/AIDS often experience stigma and discrimination from both society and their families, which may lead to social withdrawal, feelings of shame, and deterioration in their overall health and well-being. Family support, as the closest source of social support, plays a crucial role in improving the quality of life of children living with HIV/AIDS. This study aimed to analyze the relationship between family support and the quality of life of pediatric patients living with HIV/AIDS. A descriptive correlational study with a cross-sectional design was conducted. Data were collected using structured questionnaires from 30 respondents aged 10–18 years. The results showed that 17 respondents received high levels of family support, while 16 respondents had a good quality of life. Spearman's rank correlation test revealed a statistically significant relationship between family support and the quality of life of children living with HIV/AIDS at the Akar Cinta Kasih Foundation (p < 0,001). The findings indicate a positive association between family support and the quality of life of pediatric patients living with HIV/AIDS. Future studies are recommended to employ different research designs and larger sample sizes to obtain more comprehensive and generalizable findings.